Stormbreaker - Horowitz, Anthony, 1955- (New York : Philomel Books, 2001)
After the death of the uncle who had been his guardian, fourteen-year-old Alex Rider is coerced to continue his uncle's dangerous work for Britain's intelligence agency, MI6.
Wilson's Children, October 2010.
Wilson's Junior High School, November 2005.
School Library Journal, June 2001.
Books for the Teen Age (NYPL), January 2002.
Publisher's Weekly, May 2001.
Booklist, September 2001.
Keywords: Spies -- Fiction; Terrorism -- Fiction; Orphans -- Fiction; Terrorism -- Fiction; Adventure and adventurers -- Fiction; England -- Fiction